Daytime gastro-oesophageal reflux is important in oesophagitis. Issue 5 (May 1987) - de Caestecker, J S; Blackwell, J N; Pryde, A; Heading, R C
Abstract : Fifty two patients were studied to investigate the patterns of gastro-oesophageal reflux during ambulatory pH monitoring and the relationship of reflux to presence and severity of oesophagitis. Twenty nine had evidence of oesophagitis which was graded according to severity. Acid exposure (pH less than 4) was calculated in each case for the total study period, the recumbent and upright periods, and the three hour period after the evening meal. Exposure in the upright period correlated closet (r=0.92: p less than 0.001) with that during the total period. Recumbent exposure correlated with both upright and postprandial exposure (p less than 0.001). Acid exposure during all four periods correlated significantly with the severity of oesophagitis, but postprandial acid exposure correlated best and recumbent acid exposure least well. Although acid clearance in the total, recumbent and upright periods correlated with oesophagitis, postprandial clearance showed the closest relationship. Thus the magnitude of daytime reflux, especially postprandial reflux and acid clearance, is more closely related than nocturnal reflux to oesophagitis. The results do not support the contention that night time reflux is inherently more injurious than daytime reflux to the oesophageal mucosa.